Study of FSKKP portal based on Shneidermanâs eight golden rules - Ooi Boon, Khuan (2013)
Shneiderman's Eight Golden Rules is the choice of design principle for the design in this project. This project at the end will produce one prototype web portal for FSKKP to replace the current portal. The aim of this project is to develop a new web portal based on the rules by Shneiderman which the web portal produce will met all the design rules proposed by Shneiderman. Shneidermanâs Eight Golden Rules is one of the design principles falls under the scope of Human Computer Interaction. In Human Computer Interaction, there are different set of design principles proposed by various researchers worldwide and the Shneidermanâs rules is aim for the interface design of a system such as the consistency of the interface, error handling functionality and so on. In this project, the rules will be studied before any implementation is executed. Then the current web portal of FSKKP will be taken as the base design of the new portal. The system function of the web portal and the data will remain the similar, the only differences is the interface and the responses in term of usability, flexibility, robustness, etc. After the prototype had been build, survey and testing session will carry out to obtain the response of the prototype from the users. The expected result from the survey done will be a positive result where users are happy and welcome the new designed portal as the main portal for FSKKP. At the end, this research have proven that Shneidermanâs Eight Golden Rules is a very suitable set of design rules for design interface for any systems worldwide and the similar type of research on this rules should be execute in future to ensure the system build is usable, user-friendly to human and the environment.